CLINICAL AND PARACLINICAL CHARACTERISTICS OF ACUTE CALCULOUS CHOLECYSTITIS IN ELDERLY PATIENTS AT VIET NAM – SWEDEN GENERAL HOSPITAL UONG BI (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of acute calculous cholecystitis in elderly patients at Viet Nam – Sweden General Hospital Uong Bi.Methods: A cross-sectional descriptive study combining retrospective and prospective data was conducted on 85 patients aged ≥60 years diagnosed with acute calculous cholecystitis from June 2022 to June 2025 at Viet Nam – Sweden General Hospital Uong Bi.Results: The mean age was 73.7 ± 6.7 years, with a female-to-male ratio of 1.2:1. All patients had comorbidities, of whom 91.8% had at least two chronic diseases; cardiovascular diseases accounted for 97.6%. Right upper quadrant abdominal pain was present in 94.1% of cases, and 37.6% had systemic inflammatory response syndrome. Murphy’s sign was positive in 27.1%, and right upper quadrant abdominal guarding was observed in 29.4%. Leukocytosis (>10 G/L) was found in 51.6% of patients. Abdominal ultrasonography and computed tomography (CT) exhibit high diagnostic sensitivity and specificity for the detection of cholelithiasis and acute cholecystitis. According to the Tokyo Guidelines 2018 severity grading, grade I and II accounted for 84.7% of cases.Conclusion: Acute calculous cholecystitis in elderly patients commonly occurs in those with multiple comorbidities and often presents with atypical clinical features. Combined clinical and paraclinical assessment is essential for early diagnosis.
Keywords: acute cholecystitis, gallstones, elderly patients